Hadoop ji shu shou ce di san ban - White, Tom (GoTop Information, Inc., 2013)
Detailed summary in vernacular field.
Translation of: Hadoop : the definitive guide, 3rd edition. - Includes index
Keywords: Apache Hadoop; Electronic data processing -- Distributed processing; File organization (Computer science); Cloud computing; Traitement réparti; Fichiers (Informatique); Organisation; Infonuagique; Electronic data processing; Distributed processing